Technical challenges of working with extracellular vesicles - Ramirez, M; Amorim, M; Gadelha, C; Milic, I; Welsh, J; Freitas, V; Nawaz, M; Akbar, N; Couch, Y; Makin, L; Cooke, F; Vettore, A; et al. (Royal Society of Chemistry, 2017)
Extracellular Vesicles (EVs) are gaining interest as central players in liquid biopsies, with potential applications in diagnosis, prognosis and therapeutic guidance in most pathological conditions. These nanosized particles transmit signals determined by their protein, lipid, nucleic acid and sugar content, and the unique molecular pattern of EVs dictates the type of signal to be transmitted to recipient cells. However, their small sizes and the limited quantities that can usually be obtained from patient-derived samples pose a number of challenges to their isolation, study and characterization. These challenges and some possible options to overcome them are discussed in this review.